Penerapan Pendidikan Kesehatan dengan Media Lembar Balik untuk Meningkatkan Pengetauan Ibu tentang Menopause pada Wanita Pre Menopause - Hilya Fajriyani Aisyah; Hastin Ika Indriyastuti (Prosiding University Research Colloquium, 2019)
WHO predicts that there will be an increase of the number of women who experience menopause in Indonesia in 2025. This may decrease their life quality. This condition is strongly influenced by their response or reaction to that phase. Good knowledge about menopause is in need for them to prepare themselves in the face of menopause. Therefore, the writer is interested in using flipchart in applying health education about menopause for improving knowledge of pre-menopausal women. The objective of this study are knowing the application of health education using flipchart media about menopause in the effort of improving knowledge of pre-menopausal women about menopause. This study is a qualitative descriptive with a case study approach. This study was conducted from February to March 2019 and the participants were 5 pre-menopausal women. After having health education about improving the knowledge of pre-menopausal women about menopause using flipchart, there was an improvement in knowledge. i.e. from bad knowledge becomes good knowledge (3 participants), and fair knowledge becomes good knowledge (2 participants). Health education using flipchart media can improve knowledge of pre-menopausal women about menopause.